Answer:
7x⁴ + 5x³ + 7x² + 6x + 5
Step-by-step explanation:
The given expression is
(5x4 + 5x3 + 4x - 9) + (2x4 + 7x2 + 2x + 14)
The first step is to open the brackets by multiplying each term inside each bracket by the term outside each bracket. Since the term outside each bracket is 1, the expression becomes
5x⁴ + 5x³ + 4x - 9 + 2x⁴ + 7x² + 2x + 14
We would collect like terms by combining each term with the same exponent or raised to the same power. The term would be arranged in decreasing order of the exponents. It becomes
5x⁴ + 2x⁴ + 5x³ + 7x² + 4x + 2x - 9 + 14
7x⁴ + 5x³ + 7x² + 6x + 5
Answer:
coefficient of x: 2
coefficient of y: 3
coefficient of z: -7
Step-by-step explanation:
To solve this problem, first we need to sum the polynomials A and B, then we need to check the coefficients of x, y and z.
The sum of the polynomials is:
A + B = 5z + 4x^2 - 6y + 2 + 2x + 9y - 12z - 2
A + B = 4x^2 + 2x + 3y - 7z
So, the coefficients are:
coefficient of x^2: 4
coefficient of x: 2
coefficient of y: 3
coefficient of z: -7
No, Rays go one way only since a point block te other way. Otherwise it wont be a ray :)
Answer:
= 5n - 2
Step-by-step explanation:
The nth term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Given a₄ = 18 , then
a₁ + 3d = 18 , that is
3 + 3d = 18 ( subtract 3 from both sides )
3d = 15 (divide both sides by 3 )
d = 5
Then
= 3 + 5(n - 1) = 3 + 5n - 5 = 5n - 2 ← explicit rule
Answer:
1.False
2.False
3.True
4.True
5.not sure, it could be true or false because adjacent angles can add up to 180 or even 360 as long as they have the same vertex